2021
DOI: 10.3892/etm.2021.10536
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of miR‑483‑5p in patients with asymptomatic carotid artery stenosis and its predictive value for cerebrovascular event occurrence

Abstract: MicroRNAs (miRNAs/miRs) may be used as novel promising diagnostic and prognostic biomarkers for various diseases, including asymptomatic carotid artery stenosis (ACAS). The present study aimed to investigate the abnormal expression of microRNA-483-5p (miR-483-5p) in patients with ACAS and to evaluate its diagnostic value for ACAS screening and its predictive value for cerebrovascular events. A total of 128 patients with ACAS and 76 healthy controls were included in the present study. The expression of miR-483-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Increased serum miR-483-5p expression was also reported in patients with asymptomatic carotid artery stenosis compared with controls. At the same time, serum miR-483-5p expression was an independent predictive factor for the occurrence of an acute cerebrovascular event in patients with asymptomatic carotid artery stenosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum miR-483-5p expression was also reported in patients with asymptomatic carotid artery stenosis compared with controls. At the same time, serum miR-483-5p expression was an independent predictive factor for the occurrence of an acute cerebrovascular event in patients with asymptomatic carotid artery stenosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Li et al analyzed expression levels of miR-483-5p in patients with asymptomatic ICAS and evaluated its diagnostic and predictive value for IS [ 127 ]. The results revealed that patients with high miR-483-5p levels had higher a risk of IS (log-rank p = 0.011), as compared to patients with lower miR-483-5p expression levels (HR 2.670; 95% CI 1.099–6.484; p = 0.030) [ 127 ]. Similarly, miR-342-5p was proposed as an IS risk predictor at a 5 year follow-up by Zhou et al [ 128 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...mentioning
confidence: 99%
“…miR-106-5p was also significantly upregulated in the serum of ACAS patients, which could regulate cholesterol efflux targeting ABCA1 [80,86]. miR-483-5p has also been found to be increased in the serum of ACAS patients versus healthy controls, and its underlying regulatory pathway could be the regulation of high cholesterol by targeting proprotein convertase subtilisin/kexin type 9 (PCSK9), affecting the development of ACAS [87]. Moreover, upregulation of miR-92a could also be a non-invasive serum biomarker for ACAS, which might be involved in the inflammatory response by enhancing nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) [71,88] in the dysregulation of endothelial progenitor cells by targeting growth differentiation factor 11 (GDF11) via the SMAD2/3/FAK/AKT/eNOS pathway [71,89] and in the progression of atherosclerosis through the targeting of ABCA1 [71,90], as mentioned above for miR-106-5p.…”
Section: Mirnasmentioning
confidence: 99%
“…In addition, the Kaplan-Meier method has been used to assess the predictive value of the occurrence of cerebrovascular ischaemic events (CIE) in some of the miRNAs discussed above. Multivariate Cox regression analysis suggests that altered serum levels of miR-186-5p [74], miR-106-5p [80], miR-483-5p [87], miR-92a [71], miR-342-5p [69], and miR-9-5p [75] could predict the risk of future cerebrovascular events. This would mean that they might also be valuable predictors of CIE and instability.…”
Section: Mirnasmentioning
confidence: 99%